Results from Bottom Trawl Survey of Flemish Cap in July 1998 - Vázquez, Antonio (Northwest Atlantic Fisheries Organization, 1999)
37 páginas, 7 figuras, 29 tablas.-- Scientific Council Meeting A stratified random bottom trawl survey of Flemish Cap was carried out in July 1998 up to a depth of 730 metres. Survey results are presented and compared with results of previous surveys in the series since 1988. Abundance at age indices are presented for cod, American plaice, redfish (Sebastes mentella and S. fasciatus) and Greenland halibut This study was supported by the European Commission (DG XIV, Study 96-030), CSIC, IEO, IPIMAR and the Basque Government Peer reviewed